2018
DOI: 10.1186/s12913-018-3740-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy-based hypertension care employing mHealth in Lagos, Nigeria – a mixed methods feasibility study

Abstract: BackgroundAccess to quality hypertension care is often poor in sub-Saharan Africa. Some community pharmacies offer hypertension monitoring services, with and without involvement of medical doctors. To directly connect pharmacy staff and cardiologists a care model including a mobile application (mHealth) for remote patient monitoring was implemented and pilot tested in Lagos, Nigeria. Pharmacists provided blood pressure measurements and counselling. Cardiologists enrolled patients in the pilot program and remot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(115 citation statements)
references
References 29 publications
0
115
0
Order By: Relevance
“…The characteristics of the included articles are summarised in Table 2. The 10 included articles comprised three qualitative studies (1,117,118), four cluster randomized control trial (4,11,14,17), one quantitative study (121), and two mixed method studies (119,120). All the included articles were published in English language from 2010 to 2019.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
See 4 more Smart Citations
“…The characteristics of the included articles are summarised in Table 2. The 10 included articles comprised three qualitative studies (1,117,118), four cluster randomized control trial (4,11,14,17), one quantitative study (121), and two mixed method studies (119,120). All the included articles were published in English language from 2010 to 2019.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…None of the 10 included primary studies reported evidence on mHealth for disease diagnosis by health workers in SSA. In terms of geographical settings, five of the 10 includes studies were conducted in urban settings (17,(118)(119)(120)(121); three studies were conducted in semi-urban settings (1,14,117); one study was conducted in rural settings (11), and only one study was conducted in rural, semi-urban and urban settings (4). Figure 3 shows the distribution of included studies by geographical settings.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
See 3 more Smart Citations